Media Talk and Political Elections in Europe and America
X, 257 p.
Keywords: This book makes an important contribution to the study of political communication. Its chapters analyse forms of media talk associated with contemporary political elections. Key topics include: changing forms of political interview, televised political debates, and the use of multimedia in promotional discourse.